Blood coagulation times in the European brown hare (Lepus europaeus) - Pikula, Jiri; Adam, Vojtech; Bandouchova, Hana; Beklova, Miroslava; Horakova, Jana; Horakova, Hana; Kizek, Rene; Krizkova, Sona; Skocovska, Blanka; Supalkova, Veronika; Svoboda, Michal; Tremi, Frantisek; et al. (Veterinary clinical pathology, 2007)
BACKGROUND: Many causes of mortality in the European brown hare, such as bacterial and viral infections, anticoagulant poisoning, and trauma, may result in hemorrhage. There are, however, no reference values concerning blood clotting in this species. OBJECTIVES: The aim of this study was to determine reference values for blood coagulation times and related parameters in healthy European brown hares. METHODS: Blood samples from 30 clinically healthy adult hares (15 males and 15 females) were obtained. Hares were physically restrained for blood collection from the cephalic vein into tubes containing citrate and EDTA. RESULTS: Mean +/- SD were obtained for thrombin time (TT) (13.97 +/- 1.37 seconds), prothrombin time (PT) (13.32 +/- 2.15 seconds), activated partial thromboplastin time (APTT) (16.73 +/- 1.86 seconds), fibrinogen concentration (2.98 +/- 1.06 g/L), and platelet count (355.28 +/- 128.73 x 10(9)/L). CONCLUSIONS: Reference values for blood coagulation times and other parameters associated with blood clotting will be useful in the laboratory evaluation of hemorrhage in the European brown hare.
Keywords: ženské pohlaví; Female; Animals; Male; Reference Values; zajíci; referenční hodnoty; mužské pohlaví; Hares; zvířata; koagulační čas plné krve; Whole Blood Coagulation Time